2019
DOI: 10.3389/fncel.2019.00100
|View full text |Cite
|
Sign up to set email alerts
|

Alfaxalone Causes Reduction of Glycinergic IPSCs, but Not Glutamatergic EPSCs, and Activates a Depolarizing Current in Rat Hypoglossal Motor Neurons

Abstract: We investigated effects of the neuroactive steroid anesthetic alfaxalone on intrinsic excitability, and on inhibitory and excitatory synaptic transmission to hypoglossal motor neurons (HMNs). Whole cell recordings were made from HMNs in brainstem slices from 7 to 14-day-old Wistar rats. Spontaneous, miniature, and evoked inhibitory post-synaptic currents (IPSCs), and spontaneous and evoked excitatory PSCs (EPSCs) were recorded at –60 mV. Alfaxalone did not alter spontaneous glycinergic IPSC peak amplitude, ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
(93 reference statements)
1
5
0
Order By: Relevance
“…Several recent studies show that in the adult, there are indications that ethanol could have positive effects particularly for the traumatized brain [ 3 – 10 , 50 ]. Some of the mechanisms proposed to mediate this positive effect of low concentrations of ethanol are to suppress apoptosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies show that in the adult, there are indications that ethanol could have positive effects particularly for the traumatized brain [ 3 – 10 , 50 ]. Some of the mechanisms proposed to mediate this positive effect of low concentrations of ethanol are to suppress apoptosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, these studies found a strong correlation between low intake and lower risk and severity of post-ischemic injury. Both effects in apoptosis and inflammation are proposed to be involved in the mechanism in rodents [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesised that the central nervous effects may be linked to synaptic plasticity and neuromodulation at the GABA A and glycine receptor. Lau et al (2010) reported that in an in vitro hypoglossal nerve model, alfaxalone reduces glycinergic inhibitory transmission which made the nerve more "accessible" to…”
Section: Discussionmentioning
confidence: 99%
“…Glycinergic inhibitory synaptic transmission is prevalent in the brainstem and spinal cord [ 17 , 21 , 22 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ], although some other brain areas also demonstrate functional glycinergic transmission [ 90 ]. The ionotropic actions of glycinergic neurotransmission are mediated by the glycine receptor ( Figure 2 ) and plays an important role in modulating motor patterns and motor circuit interneurons and MNs [ 90 , 99 , 100 , 101 ].…”
Section: Inhibitory Neurotransmissionmentioning
confidence: 99%
“…Despite the cortical and pattern-generator (brainstem or spinal segment) influence on motor unit activation and the interactions of cerebellar and striatal regions on motor output, the MN is eminently capable of neural computation [ 12 , 13 ]. Indeed, the MN is the final common pathway, and receive excitatory (predominantly glutamatergic) inputs and both GABAergic and/or glycinergic inhibitory inputs, amongst a host of other extrinsic and intrinsic excitability modulators [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. A simplified summary of neuromotor control shows key differences between respiratory and locomotor circuits ( Figure 1 ), with respiratory circuits governed by a centralized pattern/rhythm generator (the pre-Bötzinger complex) [ 10 , 31 ] and locomotor circuits with distributed pattern generation at various segments of the brainstem and spinal cord [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%